Cross-border lending contagion in multinational banks - Alexis Derviz; Jirí Podpiera (European Central Bank (ECB), 2007)
We study both theoretically and empirically the inter- dependence of lending decisions in different country branches of a multinational bank. First, we model a bank that delegates the management of its foreign unit to a local manager with non-transferable skills. The bank differs from other international investors due to a liquidity threshold which induces a depositor run and a regulatory action if attained. A separate channel of shock propagation exists since lending decisions are influenced by delegation and precautionary motives. This can entail “contagion”, i.e. parallel reactions of the loan volumes in both countries to the parent bank home country disturbance. Second, we look for the presence of lending contagion by panel regression methods in a large sample of multinational banks and their affiliates. We find that the majority of multinational banks behave in line with contagion effect. In addition, the presence of contagion seems to be related to the geographical location of subsidiaries.
Keywords: F37; G21; G28; G31; 330; delegation; diversification; lending contagion; Multinational bank; panel regression; Internationale Bank; Ausländische Tochtergesellschaft; Kreditgeschäft; Kreditrisiko; Ansteckungseffekt; Theorie; Welt